Aproximación a un modelo didáctico con el uso de libros digitales para la potenciación de la comprensión lectora en estudiantes de 7º grado de Básica Secundaria de la I.E.T.C.S. (2019)
The present work was proposed to design the approach to a didactic model with the use of digital books for the empowerment of reading comprehension in 7th grade students of secondary school of the IETCS, based on the main contributions of the Ministry of National Education (2015), Monereo (2003), Herrera, Gregori, Sambiás, Sevilla, Montes and Abellán (2009) and others. The study was framed in the empiricist paradigm, responding to the typology of pre-experimental research, with the use of the standard questionnaire of the Colombian Institute for the Evaluation of Education (2015) to measure reading comprehension in grade 7 of the IETCS, a Through a pre-test and post-test after the implementation of Cuadernia, as a digital book tool aimed at the 38 students in total corresponding to the selected population. As a result of the first application, a general average of 4.6 points was obtained and only 13 students passed, so the intervention was developed to subsequently obtain an average of 8 points and 35 approved with the post-test. This allowed us to recognize that the use of digital books with Cuadernia enhances reading comprehension in students